T-CREo: A Twitter Credibility Analysis Framework - Cardinale, Yudith (2021)
This research was supported by the FONDO NACIONAL DE DESARROLLO CIENTIFICO, TECNOLOGICO Y DE INNOVACION TECNOLOGICA ~ FONDECYT as an executing entity of CONSEJO NACIONAL DE CIENCIA, TECNOLOGIA E INNOVACION TECNOLOGICA - CONCYTEC under grant agreement No. 01-2019-FONDECYT-BM-INC.INV in the project RUTAS: Robots for Urban Tourism centers, Autonomous and Semantic-based.